Meu subsolo por uma utopia! meu subsolo por uma utopia! tensões e desdobramentos do Niilismo na obra de Dostoiévski - Ferreira, Willian dos Santos (2019)
During the nineteenth century mainly in Czarist Russia, Nihilism became a force that took possession of the imaginary and the questions that formed Russian Intelligentsia in the Period. One of the main interpreters of nihilism and its unfolding in modernity was the writer Fyodor Dostoevsky (1821- 1881) who sees in nihilism and modernity those responsible for the detachment of Man with God and his fellow men. For this reason his works seek to disentangle the influences of nihilism mainly on the most intimate relationships that the individual can have - that is, the individual with himself, so as to think about the possibility of reestablishing lasting bonds with his "brothers". In this way the research tries to think about the role that the concept exerts in the work of Dostoyevsky and how it is necessary to think the disenchantment that plagues the reality